Toksisitas Oligomer Kitosan Derajat Deasetilasi Rendah Enzimatis Menggunakan Metode Brine Srimp Lethality Test (BSLT) - Sarni, Sarni (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2017)
Chitosan oligomers or chitooligomer is a mixture of oligomers of D-glucosamine which are formed through a process of depolymerization of chitosan with cuting its Î²-glycosidic bonding. Chitosan oligomer has received much attention in various fields because of the specific biological activity 10 times greater than chitosan. Chitosan oligomer having biological activity as antibacterial, antiviral, antioxidant, anti-tumor and anti-cancer. Before it is applied to humans, the bioactive compounds to be used as pharmaceutical products must pass a preliminary test using test animals. BSLT method is often used to praskrining against bioactive compounds. This method uses shrimp larvae are widely used in searches that are toxic bioactive compounds from natural materials. This study aims to determine the toxicity of chitosan oligomers enzymatic (crude) as a preliminary test before being used as a pharmaceutical product either as anti-cancer or anti microbial with BSLT method. The results showed chitosan oligomer (crude) hydrolysis of leather tiger shrimp chitosan (DD 60%) with chitosanase enzyme for each time of incubation has strong toxicity properties with a value of 36.90 ppm LC50 (1 hour incubation); 47.43 ppm (incubation 2 hours) and 104.86 ppm (incubation 3 hours).